An Examination of the Merits of the Use of Social Media for Dacwah Activities - Abdulsalam, Daud Olalekan; Saheed Adewale Badmus (Penerbit Hellow Pustaka, 2025)
Social media has become a dominant medium for communication and information exchange in contemporary societies, significantly influencing religious discourse and practice. In the context of Islam, social media platforms have emerged as important tools for Dacwah (Islamic propagation), enabling scholars and preachers to reach diverse audiences across geographical and cultural boundaries. This study examines the merits of the use of social media for Dacwah activities, with particular attention to its role as a source of Islamic knowledge, its wide audience coverage, its contribution to the protection of Muslim rights, its effectiveness in clarifying misconceptions about Islam, its use in fundraising for humanitarian causes, and its facilitation of marriage matchmaking in line with Islamic principles. The study adopts a qualitative research design based on an extensive review and content analysis of relevant scholarly literature, journal articles, books, and credible online sources. Findings reveal that social media enhances access to Islamic knowledge, strengthens engagement between scholars and followers, counters negative stereotypes about Islam, supports charitable initiatives, and provides alternative platforms for lawful matrimonial connections. The study concludes that social media, when responsibly and ethically utilized, offers significant opportunities for effective Dacwah in the modern age. It therefore recommends that qualified Muslim scholars intensify their engagement with social media platforms to promote authentic Islamic teachings and positively influence global perceptions of Islam.